Avaliação da pirólise assistida por micro-ondas para produção de gás, óleo pirolítico e sólido a partir de resíduos de poliuretano - Jacobi, João Vítor (2024)
The present work has used a microwave-assisted pyrolysis system with in loco heating catalyzed with graphite powder to improve the production of gas, pyrolysis oil and solid from flexible foam of polyurethane. A domestic microwave oven was adapted allowing the reactor to be inserted into the cavity. The system was made inert with argon at 0.3 L min-1 of constant flow rate. The oil formed in the process was condensed in a metal coil immersed in ice bath. At the end, the oil was extracted using dicloromethane and compressed air. The non-condensable gases were partly collected for later analysis and the rest was disposed of through the exhaust system. The system was connected to a digital controller which monitored the temperature using a thermocouple and controlled the irradiation. With the system set up, temperatures of 350, 450 and 670 °C were evaluated for 10 min, with a final cleaning step of 2 min at 670 °C. The oil and gas yields differed between the temperatures of 350 and 450 to 670 °C. In addition, water, acidity and pyrolysis oil composition were characterized, as well as the morphology of the solid fraction and the composition of the gas fraction, comparing the results with conventional heating systems. It was concluded that heating graphite using microwave radiation in direct contact with the sample was efficient and helped in the formation of value-added products from PU waste.